Trajetórias e memórias dos Fóruns Lixo e Cidadania no Brasil: experimentos singulares de justiça social e governança participativa. - Sonia Maria Dias (2009)
The main theme of this thesis is the Waste and Citizenship Forums (amultistakeholder forum) with the main objective of understanding whether its existence is really making a difference on the improvement of standards in solid waste management (SWM) in its environmental and social aspects. In doing so it seeks to deepen the understanding of the rules that structure participation at the forums; assess the progress towards eradication of open dumps and social inclusion and assess what role have the forums played in it (if any); to assess potential and constraints in the forums ability to influence public policies in solid wastes and to assess how inclusive are the Forums towards social inclusion of non-organized waste pickers and other informal sector workers within the SWM. The thesis articulates two main theoreticalframeworks: (¹) Nancy Fraser´s (2007) discussion within the paradigm ofredistribution-recognition-representation, in order to interpret the waste and citizenship under the theme of social justice, and (²) Fung and Wright´s (2001) discussion on Empowered Participatory Governance (EPG) experiments in order to investigate the effectiveness of this Forum in terms of problem solving in SWM and in producing fair and equitable outcomes for waste pickers. It is based on multiple-case studies incorporating three analytical levels: the national arrangement (the National Waste and Citizenship Forum); a state arrangement (the Waste and Citizenship Forum of Minas Gerais State) and a municipal level (Belo Horizonte). The methodology applied is qualitative (with the use of semi-structured interviews; direct observation; document analysis;exam/analysis of official data bank on waste picking activities). It was found that the Waste and Citizenship Forum helped to give more visibility to the social and environmental importance of the work carried out by the waste pickers and brought, also, the existing cooperatives and associations into the spotlight. Some of the challenges identified refer to the need of creating a framework of social and environmental indicators to assess public policies in solid waste management, the inclusion of other groups of informal workers within the SWM and to resume the campaign for eradication of child labour at open dumps.